LiFE with Archie - Reit, Sy, (Seymour); Doyle, Frank; Bob White ([New York] : Archie Comic Publications, Inc., 2020)
"LIFE WITH ARCHIE VOL. 2 is the second of a chronological collection of titles featuring the classic series. This is presented in the new higher-end format of Archie Comics Presents, which offers 200+ pages at a value while taking a design cue from successful all-ages graphic novels. The original Life with Archie series was home to the wildest alternate reality takes on the Riverdale gang. From spies to superheroes, this comic showcased stories readers never dreamed of! Relive those far-out tales in the first volume of this collection."--Provided by publisher.
Keywords: Andrews, Archie -- (Fictitious character) -- Comic books, strips, etc; Cooper, Betty -- (Fictitious character) -- Comic books, strips, etc; Lodge, Veronica -- (Fictitious character) -- Comic books, strips, etc